Phagocytosis by Thrombocytes is a Conserved Innate Immune Mechanism in Lower Vertebrates - Nagasawa, Takahiro; Nakayasu, Chihaya; Rieger, Aja M.; Barreda, Daniel R.; Somamoto, Tomonori; Nakao, Miki (Frontiers in Immunology, 2014)
Thrombocytes, nucleated hemostatic blood cells of nonmammalian vertebrates, are regarded as the functional equivalent of anucleated mammalian platelets. Additional immune functions, including phagocytosis, have also been suggested for thrombocytes, but no conclusive molecular or cellular experimental evidence for their potential ingestion and clearance of infiltrating microbes has been provided till date. In the present study, we demonstrate the active phagocytic ability of thrombocytes in lower vertebrates using teleost fishes and amphibian models. Ex vivo, common carp thrombocytes were able to ingest live bacteria as well as latex beads (0.5–3 μm in diameter) and kill the bacteria. In vivo, we found that thrombocytes represented nearly half of the phagocyte population in the common carp total peripheral blood leukocyte pool. Phagocytosis efficiency was further enhanced by serum opsonization. Particle internalization led to phagolysosome fusion and killing of internalized bacteria, pointing to a robust ability for microbe elimination. We find that this potent phagocytic activity is shared across teleost (Paralichthys olivaceus) and amphibian (Xenopus laevis) models examined, implying its conservation throughout the lower vertebrate lineage. Our results provide novel insights into the dual nature of thrombocytes in the immune and homeostatic response and further provide a deeper understanding of the potential immune function of mammalian platelets based on the conserved and vestigial functions.